Taxation and the Multinational Firm - Peter Egger; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2017)
This chapter provides a survey of issues which emerge with the taxation of multinational enterprises. It addresses tax rates which affect multinational firms directly and focuses on provisions and incentives which relate to the profits and investments of such firms directly. It survey positive as well as normative principles of such taxation and incentives, relates to tax-avoidance practices, and discusses their remedies.
Keywords: F21; F23; H25; H26; 330; taxation; foreign direct investment; multinational firms